2019
DOI: 10.1080/12298093.2018.1551855
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Achlya americana and A. bisexualis (Saprolegniales, Oomycota) Isolated from Freshwater Environments in Korea

Abstract: Many members of the Saprolegniales (Oomycete) cause mycoses and disorders of fishes, of which Achlya and Saprolegnia are most ubiquitous genera worldwide. During a survey of the diversity of freshwater oomycetes in Korea, we collected seven isolates of Achlya , for which morphological and molecular phylogenetic analyses enabled them to identify as Achlya americana and Achlya bisexualis . In Korea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(36 reference statements)
0
6
0
3
Order By: Relevance
“…They are "recyclers" in that they decompose dead organic matter (Harms et al 2011, Iskandar et al 2011, Anastasi et al 2013, Tsui et al 2016, Grossart et al 2019, Gulis et al 2019. Freshwater fungi can be found in living (plants and animals) and non-living (decaying wood and leaves) substrates (Choi et al 2019, Grossart et al 2019, Tsui et al 2000. They are accommodated in eight phyla: Aphelidiomycota, Ascomycota, Basidiomycota, Blastocladiomycota, Chytridiomycota, Monoblepharomycota, Mortierellomycota and Rozellomycota (Zhang et al 2012, Bao et al 2019, Calabon et al 2020, Hyde et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They are "recyclers" in that they decompose dead organic matter (Harms et al 2011, Iskandar et al 2011, Anastasi et al 2013, Tsui et al 2016, Grossart et al 2019, Gulis et al 2019. Freshwater fungi can be found in living (plants and animals) and non-living (decaying wood and leaves) substrates (Choi et al 2019, Grossart et al 2019, Tsui et al 2000. They are accommodated in eight phyla: Aphelidiomycota, Ascomycota, Basidiomycota, Blastocladiomycota, Chytridiomycota, Monoblepharomycota, Mortierellomycota and Rozellomycota (Zhang et al 2012, Bao et al 2019, Calabon et al 2020, Hyde et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Oomycota, a monophyletic group of filamentous microbes under the kingdom Straminipila, is ubiquitous in the oceans [1,2], freshwater [3,4], and terrestrial environments [5,6] throughout the world. Aquatic oomycetes are often referred to as “water molds” and play significant roles on aquatic ecosystems, where most oomycetes are saprotrophic, responsible for decomposing and recycling of organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the traits of aquatic oomycetes regard to saprophytism and endophytism are largely unknown, in comparison with the parasitic species that infect fish, fish eggs [9,10], and algae [11,12]. In Korea, aquatic oomycetes relating to fish and algae diseases have been recently recorded, e.g., Achlya [3], Pythium [12,13], and Saprolegnia [14]. However, diversity of saprotrophic or endophytic oomycetes in Korea remains still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Oomycetes are a diverse group of filamentous eukaryotic microbiota that includes animal and plant pathogens (Gaulin et al, 2010). Many representatives of Saprolegniales (Oomycetes) cause fungal diseases of fish, among which the most common genera are Achlya and Saprolegnia (Kar, 2016;Wuensch et al, 2018;Choi et al, 2019). Oomycetes are divided into three subclasses: Saprolegniomycetidae, Rhipidiomycetidae and Peronosporomycetidae, each of them can infect a wide range of hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The most common species are S. diclina, S. ferax, S. australis and S. parasitica (Ke et al, 2009). A study performed in Korea from fish identified seven isolates of saprolegniosis pathogens, morphological and molecular phylogenetic analysis of which permitted them to be identified as Achlya americana and A. bisexualis (Choi et al, 2019). Oomycetes isolated from cichlids in South Africa have been identified as A. bisexualis (Greeff-Laubscher et al, 2019).…”
Section: Introductionmentioning
confidence: 99%